Tradeoffs between uses of crop residues a focus for SLP policy discussions - Gerard, Bruno G. (International Livestock Research Institute, 2009)
Bruno Gerard, Coordinator of the CGIAR Systemwide Livestock Programme (SLP) introduces the SLP and a major topic of discussion at the December 2009 meeting of its Livestock Programme Group: Researching tradeoffs between the uses of residues for livestock and for soil improvement.